3, 14, 19‐Triacetyl Andrographolide alleviates the cognitive dysfunction of 3 × Tg‐AD mice by inducing initiation and promoting degradation process of autophagy. (17th September 2022) - Zhang, Haiyu; Xie, Xinmei; Shi, Junzhuo; Zhao, Qian; Luo, Dongmei; Hao, Jiaojiao; Zhou, Yunfeng; Han, Guang; Pang, Xiaobin
Abstract: The present study aims to investigate the cognition‐enhancing effect of 3, 14, 19‐Triacetyl andrographolide (ADA) on learning and memory deficits in 3 × Tg‐AD mice and to explore its underlying mechanism. Eight‐month‐old 3 × Tg‐AD mice and C57BL/6J mice were randomly divided into three groups, namely wild‐type group, 3 × Tg‐AD group, and 3 × Tg‐AD+ADA group (5 mg/kg, for 21 days, i.p.). We found that ADA significantly improved learning and cognition impairment, inhibited the loss of Nissl body, and reduced Aβ load in the brains of 3 × Tg‐AD mice. In addition, ADA enhanced the levels of PSD95 and SYP, which were closely associated with synaptic plasticity. Accumulated autophagosomes, LC3II, and P62 in hippocampus and cortex of 3 × Tg‐AD mice were decreased by ADA treatment. Furthermore, ADA administration further down‐regulated the expressions of p‐AKT and p‐mTOR, reduced the level of CTSB, and increased the co‐localization of LC3 and LAMP1 in the brains of 3 × Tg‐AD mice, implying that ADA‐induced autophagy initiation and also promoted the degradation process. In Aβ25–35 ‐induced HT22 cells, ADA displayed similar effects on autophagy flux as observed in 3 × Tg‐AD mice. Our finding verified that ADA could improve synaptic plasticity and cognitive function, which is mainly attributed to the key roles of ADA in autophagy induction and degradation.